2023
DOI: 10.1177/09697330221114339
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' professional commitment in COVID-19 crisis: A qualitative study

Abstract: Background: Professional commitment is an important factor in employee performance. COVID-19 outbreak has seriously affected the nurses working conditions. Numerous factors can affect nurses' professional commitment in this situation. Aim: To explore the nurses' lived experiences, attitudes, views and perceptions toward professional commitment and factors affecting it in the Covid-19 crisis. Method, Setting and Participants: This qualitative study was conducted using phenomenological approach and content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[2] Professional commitment encompasses the positive attitudes and behaviors expressed by students who identify with their chosen field of study and are prepared to exert corresponding effort; it serves as a crucial psychological basis for a student learning initiative and enthusiasm. [3] Research has found a significant negative correlation between all dimensions of professional commitment, as well as overall professional commitment scores, and learning burnout, making professional commitment a significant predictor of learning burnout. [4] Increasing students' recognition of and emotional connection with their major can, to a certain extent, mitigate learning burnout.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Professional commitment encompasses the positive attitudes and behaviors expressed by students who identify with their chosen field of study and are prepared to exert corresponding effort; it serves as a crucial psychological basis for a student learning initiative and enthusiasm. [3] Research has found a significant negative correlation between all dimensions of professional commitment, as well as overall professional commitment scores, and learning burnout, making professional commitment a significant predictor of learning burnout. [4] Increasing students' recognition of and emotional connection with their major can, to a certain extent, mitigate learning burnout.…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic has had a serious impact on the working conditions of health workers including nurses ( Lau et al, 2021 ; Razu et al, 2021 ). Despite this, nurses with greater professional commitment will continue to work, fulfilling their duties and saving the lives of millions during this difficult time ( Duran et al, 2021 ; Momeni & Khatooni, 2023 ). Hence, most of them do their best to fulfill their job responsibilities ( Duran et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Increased workload, longer working hours, and lack of protective equipment, such as protective masks, etc. have created stressful working conditions for nurses (1,2). Long working hours are challenging beyond mere professional commitment, leading to fatigue and burnout and negatively affecting their quality of life (health, physical, psychological, environmental, and social).…”
mentioning
confidence: 99%